The Impact of Corporate Social Responsibility and Institutional Ownership on Corporate Tax Aggressiveness with Firm Size as Moderating Variable - Retnaningtyas Widuri (International Journal of Pertapsi, 2023)
This study aims to determine the relationship between corporate social responsibility and institutional ownership on tax aggressiveness, focusing on firm size as moderating variables. The population of this study were companies listed on the Indonesia Stock Exchange (IDX) during 2016 until 2020. A purposive sampling approach was used in the sample selection process for this study, and the final sample was collected by 110 companies with 520 units of analysis. In this study, hypotheses were examined using structural equation modeling. The results showed that CSR disclosure had a positive effect on tax aggressiveness. Firm size positively moderates the relationship between CSR and affects tax aggressiveness. The second result, institutional ownership has a negative effect on tax aggressiveness. Firm size positively moderates the relationship between institutional ownership and tax aggressiveness. Those academic scholars, practitioners, and regulators who are interested in uncovering corporate governance score, tax avoidance, and CSR may find these findings to be of interest. Before mandating extra governance procedures for companies operating in their nation, regulators are required to first assess the legal framework in their country as well as the actual corporate governance mechanisms already in place. This paper examines the relationship between CSR and tax avoidance with a sample of all companies listed on the IDX for five years using firm size as a moderator.